Quantifying the Role of Climate Change in Driving Mass Coral Bleaching - Andrew Pershing; John Bruno; Joseph Giguere; Alexandra Khrizman (Oceanography, 2026)
Four global mass coral bleaching events have now been recorded. The first, in 1998, was associated with that year’s strong El Niño. Subsequent global-scale bleaching occurred in 2010 and then over the periods 2014–2017 and 2018–2025 (and likely ongoing). All these events also coincided with El Niños for at least part of the period. While El Niño is an important factor, each event has also occurred during a period of rising global temperatures. Here, we use attribution of daily sea surface temperatures to show that the most recent global coral bleaching event is entirely due to human-caused warming. Furthermore, all previous events, including the original one in 1998, had strong fingerprints of anthropogenic climate change. Our analysis shows that global warming is the main driver of bleaching and that global coral bleaching simply would not occur without human-caused climate change.

Whales in the carbon cycle: can recovery remove carbon dioxide? - Heidi C. Pearson; Matthew S. Savoca; Daniel P. Costa; Michael W. Lomas; Renato Molina; Andrew J. Pershing; Craig R. Smith; Juan Carlos Villaseñor-Derbez; Stephen R. Wing; Joe Roman (Trends in Ecology & Evolution, 2024)

Early Warning of a Cold Wave in the Gulf of Maine - Nicholas Record; Andrew Pershing; Douglas Rasher (Oceanography, 2024)
Oceanographic changes are occurring more rapidly in recent decades, with new implications for ocean ecosystems and adjacent human communities. It is important to bring attention to these changes while they are unfolding rather than after they have occurred. Here we report on a rapid shift toward colder, fresher water in the deep Gulf of Maine that, as of mid-June 2024, has persisted for at least six months. The shift likely represents an influx of Labrador Slope Water and resembles conditions that predated a major warming shift that occurred in 2011–2012. Deep-water oceanographic conditions in the Gulf of Maine have a strong influence on ecosystem dynamics, including the prey of critically endangered North Atlantic right whales, the seasonal and disease dynamics of American lobster, and the distribution and abundance of kelp forest communities, among others. Oceanographic surprises have an important role in this system, and monitoring how this shift unfolds, oceanographically and ecologically, will give new insights into how oceanographic signals can inform our understanding of ecosystem responses.

Merging trait‐based ecology and regime shift theory to anticipate community responses to warming - Sarah J. Weisberg; Andrew J. Pershing; Maria Grigoratou; Katherine E. Mills; Ileana F. Fenwick; Michael G. Frisk; Richard McBride; Sean M. Lucey; Adam Kemberling; Brandon Beltz; Janet A. Nye (Global Change Biology, 2024)
Anthropogenic warming is altering species abundance, distribution, physiology, and more. How changes observed at the species level alter emergent community properties is an active and urgent area of research. Trait‐based ecology and regime shift theory provide complementary ways to understand climate change impacts on communities, but these two bodies of work are only rarely integrated. Lack of integration handicaps our ability to understand community responses to warming, at a time when such understanding is critical. Therefore, we advocate for merging trait‐based ecology with regime shift theory. We propose a general set of principles to guide this merger and apply these principles to research on marine communities in the rapidly warming North Atlantic. In our example, combining trait distribution and regime shift analyses at the community level yields greater insight than either alone. Looking forward, we identify a clear need for expanding quantitative approaches to collecting and merging trait‐based and resilience metrics in order to advance our understanding of climate‐driven community change.

Whales in the carbon cycle: can recovery remove carbon dioxide? - Heidi C. Pearson; Matthew S. Savoca; Daniel P. Costa; Michael W. Lomas; Renato Molina; Andrew J. Pershing; Craig R. Smith; Juan Carlos Villaseñor-Derbez; Stephen R. Wing; Joe Roman (Trends in Ecology & Evolution, 2023)

Implications of fisheries allocation policy on anticipated climate change impacts - Kanae Tokunaga; Lisa A. Kerr; Andrew J. Pershing (Marine Policy, 2023)

Optimizing fisheries for blue carbon management: Why size matters - Jonathan E. Falciani; Maria Grigoratou; Andrew J. Pershing (Limnology and Oceanography, 2022)
Fish contribute to the export of carbon out of the euphotic zone. They ingest organic carbon fixed by phytoplankton, store it in their tissues for their lifetime, and contribute to long‐term sequestration by producing sinking fecal pellets, respiring at depth, or via their own sinking carcasses. While the flux of carbon through fish is small relative to the export flux by plankton, humans have a direct influence on fish communities and thus on the magnitude of carbon storage and flux. We use a size spectrum model to examine the combined effect of fishing and trophic dynamics on the total carbon stored as biomass of a simulated community of fish. By sampling 10,500 possible fishing strategies that randomize fishing mortality and size‐selectivity, we consider optimal strategies that balance several UN Sustainable Development Goals addressing (1) food security, (2) climate action, and (3) marine conservation. The model shows that fishery management strategies that preferentially conserve large species increase overall carbon stored in the fish community. This study presents a perspective for considering carbon storage and sequestration in fisheries management alongside alternative objectives such as food production and biodiversity conservation. Our study focused on the state (total carbon in the living community). Incorporating rate processes like fecal pellet flux, vertical migration, and natural mortality would build toward a more holistic carbon approach to fisheries management.

Facing the Forecaster’s Dilemma: Reflexivity in Ocean System Forecasting - Nicholas R. Record; Andrew J. Pershing (Oceans, 2021)
Unlike atmospheric weather forecasting, ocean forecasting is often reflexive; for many applications, the forecast and its dissemination can change the outcome, and is in this way, a part of the system. Reflexivity has implications for several ocean forecasting applications, such as fisheries management, endangered species management, toxic and invasive species management, and community science. The field of ocean system forecasting is experiencing rapid growth, and there is an opportunity to add the reflexivity dynamic to the conventional approach taken from weather forecasting. Social science has grappled with reflexivity for decades and can offer a valuable perspective. Ocean forecasting is often iterative, thus it can also offer opportunities to advance the general understanding of reflexive prediction. In this paper, we present a basic theoretical skeleton for considering iterative reflexivity in an ocean forecasting context. It is possible to explore the reflexive dynamics because the prediction is iterative. The central problem amounts to a tension between providing a reliably accurate forecast and affecting a desired outcome via the forecast. These two objectives are not always compatible. We map a review of the literature onto relevant ecological scales that contextualize the role of reflexivity across a range of applications, from biogeochemical (e.g., hypoxia and harmful algal blooms) to endangered species management. Formulating reflexivity mathematically provides one explicit mechanism for integrating natural and social sciences. In the context of the Anthropocene ocean, reflexivity helps us understand whether forecasts are meant to mitigate and control environmental changes, or to adapt and respond within a changing system. By thinking about reflexivity as part of the foundation of ocean system forecasting, we hope to avoid some of the unintended consequences that can derail forecasting programs.

Can Right Whales Out-Swim Climate Change? Can We? - Andrew Pershing; Daniel Pendleton (Oceanography, 2021)
The article by Meyer-Gutbrod and colleagues in this issue demonstrates that the endangered North Atlantic right whale’s preferred prey has declined as the Northwest Atlantic has warmed. Right whales are now spending more time foraging in historically colder habitats, but they are producing fewer calves. The low calf production could reflect a delay between the decline in the potential productivity of their traditional habitats and its increase in their new habitats. This delay would result in a “climate deficit” in their fitness. Right whales must also learn to forage successfully in their new habitats, creating an additional loss of fitness termed an “adaptation deficit.” Humans will also face unavoidable climate deficits, but we have more options for minimizing adaptation deficits.

Rapid Climate-Driven Circulation Changes Threaten Conservation of Endangered North Atlantic Right Whales - Nicholas Record; Jeffrey Runge; Daniel Pendleton; William Balch; Kimberley Davies; Andrew Pershing; Catherine Johnson; Karen Stamieszkin; Rubao Ji; Zhixuan Feng; Scott Kraus; Robert Kenney; et al. (Oceanography, 2019)

Modeling marine pelagic fish species spatiotemporal distributions utilizing a maximum entropy approach - Lifei Wang; Lisa A. Kerr; Nicholas R. Record; Eric Bridger; Benjamin Tupper; Katherine E. Mills; Edward M. Armstrong; Andrew J. Pershing (Fisheries Oceanography, 2018)
Understanding how ocean conditions influence fish distributions is critical for elucidating the role of climate in ecosystem change and forecasting how fish may be distributed in the future. Traditional species distribution models are often applied to scientific‐survey data, which include species presence‐absence information, to predict distributions. Maximum entropy (MaxEnt) models are promising tools as they can be applied to presence‐only data (e.g., data collected from fishermen targeting a specific species or from observers in citizen‐science programs). We used MaxEnt models to relate occurrence records of three marine pelagic fish (Atlantic herring, Atlantic mackerel, and butterfish) in fishery‐dependent data to environmental conditions (sea surface temperature ( SST ) and chlorophyll‐ a concentration from satellite remote sensing, bathymetry, and climate indices), and evaluated model performance by both cross‐validation and validation using fishery‐independent data. We developed monthly habitat suitability maps for these fish in the Northwest Atlantic Shelf area, and assessed the relative influence of environmental factors on their distributions. Across months, their suitable habitat areas varied with each species exhibiting inshore‐offshore and north‐south movements in response to changing environmental conditions. Overall, SST and chlorophyll‐ a concentration had the greatest influence on the distributions of these fish, with bathymetry having moderate influence and climate indices having little influence. Our application of MaxEnt models enabled us to integrate presence‐only data and high resolution environmental data from satellite remote sensing to describe spatiotemporal distributions of marine pelagic fish. These models were used to hindcast species occurrence in relation to historical environmental conditions to evaluate their predictive performance, and have the potential to provide nowcasts in relation to current conditions or forecasts of species future distributions.

Evidence for Adaptation from the 2016 Marine Heatwave in the Northwest Atlantic Ocean - Andrew Pershing; Katherine Mills; Alexa Dayton; Bradley Franklin; Brian Kennedy (Oceanography, 2018)

Forecasting the Seasonal Timing of Maine's Lobster Fishery - Katherine E. Mills; Andrew J. Pershing; Christina M. Hernández (Frontiers in Marine Science, 2017)

Effects of spring onset and summer duration on fish species distribution and biomass along the Northeast United States continental shelf - M. Elisabeth Henderson; Katherine E. Mills; Andrew C. Thomas; Andrew J. Pershing; Janet A. Nye (Reviews in Fish Biology and Fisheries, 2017)

Size as the master trait in modeled copepod fecal pellet carbon flux - Karen Stamieszkin; Andrew J. Pershing; Nicholas R. Record; Cynthia H. Pilskaln; Hans G. Dam; Leah R. Feinberg (Limnology and Oceanography, 2015)
Zooplankton fecal pellet flux is a highly variable component of the biological carbon pump. While fecal pellets can comprise 0 to nearly 100% of particulate organic carbon collected in sediment traps, mechanisms for this variability remain poorly understood. Fecal pellet carbon flux is a complex function of several variables. We present a model that incorporates individual‐scale metabolic processes to determine fecal pellet production rate, the relationship between body size and fecal pellet size, the relationship between fecal pellet size and sinking rate, and a function representing the breakdown of particles in the water column. When applied to copepod communities sampled by the continuous plankton recorder in the Gulf of Maine over 25 years, a seasonal pattern of fecal pellet carbon flux emerges. The interannual flux time series produced by the model reflects known oceanographic perturbations and shows how organism‐scale processes can be scaled up to explain ecosystem level variability. We conclude that fecal pellet carbon flux in the Gulf of Maine is driven by copepod community size structure and copepod abundance, and that the fraction of fecal pellet carbon that reaches depth is a function of copepod size, rather than abundance. Changes in the physical environment which alter the size composition of the copepod community lead to variability in fecal pellet carbon flux. Our results indicate that incorporating size composition into biogeochemical models can more accurately constrain zooplankton‐mediated carbon flux.

Migration model of post‐smolt A tlantic salmon ( S almo salar ) in the G ulf of M aine - Carrie J. Byron; Andrew J. Pershing; Jason D. Stockwell; Huijie Xue; John Kocik (Fisheries Oceanography, 2014)
Understanding how oceanographic factors independently and interactively influence fish behavior, physiology, and survival is essential for predicting the impact of climate change on fish. Such predictions are especially challenging for highly migratory species such as salmon that experience a broad range of conditions. We applied a novel modeling approach that combines an individual‐based particle model with a bioenergetics model to evaluate the effects of oceanographic variability on migration of post‐smolt Atlantic salmon ( Salmo salar ). Interannual variability in the surface current velocity and sea surface temperature differentially influenced post‐smolt salmon migration. The magnitude, duration, and direction of the currents relative to a fish's intended swimming direction had the strongest influence on migration. Changes in ocean circulation led to changes in currents at a regional scale that have a similar, relative effect across multiple populations during out‐migration. Results of this study suggest that the Nova Scotia Coastal Current has a strong influence on the migration pathways of migrating salmon through the Gulf of Maine. The influx of cool fresh water from the Arctic, observed in the early 1990s, changed the Nova Scotia Coastal Current and, as suggested by model results, could have dramatically influenced post‐smolt salmon migration success. There was a trade‐off between arriving at the destination quickly but at a small size and not arriving at the destination at all. Fish that took a long time to migrate had more opportunities to feed and encountered warmer summer waters, increasing their overall growth.

Climate and ecosystem linkages explain widespread declines in North American Atlantic salmon populations - Katherine E. Mills; Andrew J. Pershing; Timothy F. Sheehan; David Mountain (Global Change Biology, 2013)
North American Atlantic salmon ( Salmo salar ) populations experienced substantial declines in the early 1990s, and many populations have persisted at low abundances in recent years. Abundance and productivity declined in a coherent manner across major regions of North America, and this coherence points toward a potential shift in marine survivorship, rather than local, river‐specific factors. The major declines in Atlantic salmon populations occurred against a backdrop of physical and biological shifts in Northwest Atlantic ecosystems. Analyses of changes in climate, physical, and lower trophic level biological factors provide substantial evidence that climate conditions directly and indirectly influence the abundance and productivity of North American Atlantic salmon populations. A major decline in salmon abundance after 1990 was preceded by a series of changes across multiple levels of the ecosystem, and a subsequent population change in 1997, primarily related to salmon productivity, followed an unusually low NAO event. Pairwise correlations further demonstrate that climate and physical conditions are associated with changes in plankton communities and prey availability, which are ultimately linked to Atlantic salmon populations. Results suggest that poor trophic conditions, likely due to climate‐driven environmental factors, and warmer ocean temperatures throughout their marine habitat area are constraining the productivity and recovery of North American Atlantic salmon populations.

Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems - Charles H. Greene; Erin Meyer-Gutbrod; Bruce C. Monger; Louise P. McGarry; Andrew J. Pershing; Igor M. Belkin; Paula S. Fratantoni; David G. Mountain; Robert S. Pickart; Andrey Proshutinsky; Rubao Ji; James J. Bisagni; et al. (Limnology and Oceanography, 2013)
Decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climate‐associated atmosphere‐ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin‐ and hemispheric‐scale changes in ocean circulation. We review and synthesize results from process‐oriented field studies and retrospective analyses of time‐series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom‐up forcing associated with climate plays a prominent role in the dynamics of these ecosystems, comparable in importance to that of top‐down forcing associated with commercial fishing. A broad perspective, one encompassing the effects of basin‐ and hemispheric‐scale climate processes on marine ecosystems, will be critical to the sustainable management of marine living resources in the Northwest Atlantic.

The biogeography of marine plankton traits - Andrew D. Barton; Andrew J. Pershing; Elena Litchman; Nicholas R. Record; Kyle F. Edwards; Zoe V. Finkel; Thomas Kiørboe; Ben A. Ward (Ecology Letters, 2013)
Changes in marine plankton communities driven by environmental variability impact the marine food web and global biogeochemical cycles of carbon and other elements. To predict and assess these community shifts and their consequences, ecologists are increasingly investigating how the functional traits of plankton determine their relative fitness along environmental and biological gradients. Laboratory, field and modelling studies are adopting this trait‐based approach to map the biogeography of plankton traits that underlies variations in plankton communities. Here, we review progress towards understanding the regulatory roles of several key plankton functional traits, including cell size, N 2 ‐fixation and mixotrophy among phytoplankton, and body size, ontogeny and feeding behaviour for zooplankton. The trait biogeographical approach sheds light on what structures plankton communities in the current ocean, as well as under climate change scenarios, and also allows for finer resolution of community function because community trait composition determines the rates of significant processes, including carbon export. Although understanding of trait biogeography is growing, uncertainties remain that stem, in part, from the paucity of observations describing plankton functional traits. Thus, in addition to recommending widespread adoption of the trait‐based approach, we advocate for enhanced collection, standardisation and dissemination of plankton functional trait data.

Fisheries Management in a Changing Climate: Lessons From the 2012 Ocean Heat Wave in the Northwest Atlantic - Katherine Mills; Andrew Pershing; Curtis Brown; Yong Chen; Fu-Sung Chiang; Daniel Holland; Sigrid Lehuta; Janet Nye; Jenny Sun; Andrew Thomas; Richard Wahle (Oceanography, 2013)

First principles of copepod development help explain global marine diversity patterns - Nicholas R. Record; Andrew J. Pershing; Frédéric Maps (Oecologia, 2012)

Large‐scale coherence in New England lobster ( Homarus americanus ), settlement and associations with regional atmospheric conditions - ANDREW J. PERSHING; RICHARD A. WAHLE; PATRICK C. MEYERS; PETER LAWTON (Fisheries Oceanography, 2012)
Time series of American lobster ( Homarus americanus ) postlarval settlement from southern New England to Atlantic Canada exhibit many common features, and a cluster analysis indicates a block of regions extending from Massachusetts to Maine that have coherent interannual variations. The spatial scale of this block suggests that variability in settlement is related to large‐scale, rather than local, processes. We examined the association between settlement at six reference regions and monthly mean atmospheric conditions (temperature, geopotential height, westerly and southerly wind components, and wind curl) from the North American Regional Reanalysis. We first extracted the dominant modes of variability in monthly averaged geopotential height, temperature, and wind curl. The leading mode from September, which represents high geopotential height, warm temperatures, and negative wind curl throughout the study area, was strongly correlated with settlement at most of the regions. The third mode from August, which represents enhanced southwesterly winds, was correlated with settlement in Rhode Island. Correlations between local atmospheric conditions and lobster settlement confirm the principal component results. Settlement was correlated to varying degrees with geopotential height (positive), temperature (positive) and wind curl (negative) with lobster settlement at the northern sites, with temperature being a stronger indicator in the north and curl a stronger indicator in the south. Rhode Island settlement was strongly correlated with August westerly winds. The correlation between settlement and atmospheric conditions could improve our understanding of stock‐recruit relationships for lobster populations and provides one mechanism for how climate change could impact lobsters.

A late Holocene paleo-productivity record in the western Gulf of Maine, USA, inferred from growth histories of the long-lived ocean quahog (Arctica islandica) - Alan D. Wanamaker; Karl J. Kreutz; Bernd R. Schöne; Kirk A. Maasch; Andrew J. Pershing; Harold W. Borns; Douglas S. Introne; Scott Feindel (International Journal of Earth Sciences, 2009)

ARCTIC CLIMATE CHANGE AND ITS IMPACTS ON THE ECOLOGY OF THE NORTH ATLANTIC - Charles H. Greene; Andrew J. Pershing; Thomas M. Cronin; Nicole Ceci (Ecology, 2008)
Arctic climate change from the Paleocene epoch to the present is reconstructed with the objective of assessing its recent and future impacts on the ecology of the North Atlantic. A recurring theme in Earth's paleoclimate record is the importance of the Arctic atmosphere, ocean, and cryosphere in regulating global climate on a variety of spatial and temporal scales. A second recurring theme in this record is the importance of freshwater export from the Arctic in regulating global‐ to basin‐scale ocean circulation patterns and climate. Since the 1970s, historically unprecedented changes have been observed in the Arctic as climate warming has increased precipitation, river discharge, and glacial as well as sea‐ice melting. In addition, modal shifts in the atmosphere have altered Arctic Ocean circulation patterns and the export of freshwater into the North Atlantic. The combination of these processes has resulted in variable patterns of freshwater export from the Arctic Ocean and the emergence of salinity anomalies that have periodically freshened waters in the North Atlantic. Since the early 1990s, changes in Arctic Ocean circulation patterns and freshwater export have been associated with two types of ecological responses in the North Atlantic. The first of these responses has been an ongoing series of biogeographic range expansions by boreal plankton, including renewal of the trans‐Arctic exchanges of Pacific species with the Atlantic. The second response was a dramatic regime shift in the shelf ecosystems of the Northwest Atlantic that occurred during the early 1990s. This regime shift resulted from freshening and stratification of the shelf waters, which in turn could be linked to changes in the abundances and seasonal cycles of phytoplankton, zooplankton, and higher trophic‐level consumer populations. It is predicted that the recently observed ecological responses to Arctic climate change in the North Atlantic will continue into the near future if current trends in sea ice, freshwater export, and surface ocean salinity continue. It is more difficult to predict ecological responses to abrupt climate change in the more distant future as tipping points in the Earth's climate system are exceeded.

THE RELATION BETWEEN PRODUCTIVITY AND SPECIES DIVERSITY IN TEMPERATE–ARCTIC MARINE ECOSYSTEMS - Jon D. Witman; Mathieu Cusson; Philippe Archambault; Andrew J. Pershing; Nova Mieszkowska (Ecology, 2008)
Energy variables, such as evapotranspiration, temperature, and productivity explain significant variation in the diversity of many groups of terrestrial plants and animals at local to global scales. Although the ocean represents the largest continuous habitat on earth with a vast spectrum of primary productivity and species richness, little is known about how productivity influences species diversity in marine systems. To search for general relationships between productivity and species richness in the ocean, we analyzed data from three different benthic marine ecosystems (epifaunal communities on subtidal rock walls, on navigation buoys in the Gulf of St. Lawrence, and Canadian Arctic macrobenthos) across local to continental spatial scales ( 1000 km) using a standardized proxy for productivity, satellite‐derived chlorophyll α Theoretically, the form of the function between productivity and species richness is either monotonically increasing or decreasing, or curvilinear (hump‐ or U‐shaped). We found three negative linear and three hump‐shaped relationships between chlorophyll α and species richness out of 10 independent comparisons. Scale dependence was suggested by more prevalent diversity–productivity relationships at smaller (local, landscape) than larger (regional, continental) spatial scales. Differences in the form of the functions were more closely allied with community type than with scale, as negative linear functions were restricted to sessile epifauna while hump‐shaped functions occurred in Arctic macrobenthos (mixed epifauna, infauna). In two of the data sets, (St. Lawrence epifauna and Arctic macrobenthos) significant effects of chlorophyll α co‐varied with the effects of salinity, suggesting that environmental stress as well as productivity influences diversity in these marine systems. The co‐varying effect of salinity may commonly arise in broad‐scale studies of productivity and diversity in marine ecosystems when attempting to sample the largest range of productivity, often encompassing a coastal–oceanic gradient.

BOOK REVIEW | Dynamics of Marine Ecosystems: Biological-Physical Interactions in the Oceans (Third Edition) - Andrew Pershing (Oceanography, 2006)

Supply-Side Ecology and the Response of Zooplankton to Climate-Driven Changes in North Atlantic Ocean Circulation - Charles Greene; Andrew Pershing; Bruce Monger; Mark Benfield; Edward Durbin; Maria Casas (Oceanography, 2004)

Impact of Climate Variability on the Recovery of Endangered North Atlantic Right Whales - Charles Greene; Andrew Pershing; Robert Kenney; Jack Jossi (Oceanography, 2003)

The flip‐side of the North Atlantic Oscillation and modal shifts in slope‐water circulation patterns - Charles H. Greene; Andrew J. Pershing (Limnology and Oceanography, 2003)
A large single‐year reversal in the phase of the North Atlantic Oscillation (NAO) during 1996 led to a dramatic shift in the slope‐water circulation patterns of the northwest (NW) Atlantic. Analyses of time‐series data collected from the region over the past half century show that both physical and biological responses are commonly elicited by such phase reversals in the NAO. Here, we use a model developed from time‐series data to predict responses of the NW Atlantic slope‐water circulation patterns to phase reversals in the NAO.

Oceanographic Responses to Climate in the Northwest Atlantic - Andrew Pershing; Charles Greene; Charles Hannah; Doug Sameoto; Erica Head; David Mountain; Jack Jossi; Mark Benfield; Philip Reid; Ted Durbin (Oceanography, 2001)